2014
DOI: 10.4028/www.scientific.net/amm.675-677.1595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Schisandra Polysaccharides on the Learning and Memory Ability in Brain Aging Mice

Abstract: This study focused on the improvement of Schisandra polysaccharide on the learning and memory in D-galactose-induced brain aging mice, to lay the foundation for the prevention and treatment of brain aging and related diseases. D-galactose was used to establish a mice brain aging model, Morris water maze and passive avoidance test were used to observe effects of Schisandra polysaccharide on the learning and memory ability of D- galactose-induced brain aging mice. The results showed that Schisandra polysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Previous studies also showed reduction of SOD and CAT activity in animal models of PQ poisoning [ 26 , 27 ], the role of free radical generation in PQ-induced injuries [ 28 ], and decreased SOD and CAT activities in animal lung tissues due to PQ administration [ 29 ]. A positive correlation between enhanced levels of oxidants and inflammatory mediators with administered PQ doses [ 30 ], increased oxidant, and decreased antioxidant markers in the hippocampus due to PQ poisoning were shown [ 6 , 31 ], which support the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies also showed reduction of SOD and CAT activity in animal models of PQ poisoning [ 26 , 27 ], the role of free radical generation in PQ-induced injuries [ 28 ], and decreased SOD and CAT activities in animal lung tissues due to PQ administration [ 29 ]. A positive correlation between enhanced levels of oxidants and inflammatory mediators with administered PQ doses [ 30 ], increased oxidant, and decreased antioxidant markers in the hippocampus due to PQ poisoning were shown [ 6 , 31 ], which support the findings of the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Treatment of PQ-exposed animals with Z. multiflora extract and pioglitazone decreased serum levels of IL-17 and TNF- α but increased IL-10 and INF- γ . The immunomodulatory effects of Z. multiflora extract were comprehensively reviewed previously [ 31 ], and the effects of the plant on various cytokine levels in animal models of asthma and COPD [ 23 ], on gene expression of various cytokine in a mouse model of asthma [ 39 ], and on different cytokines in patients with lung disorders due to sulfur mustard exposure also [ 8 ] were shown supporting the results of the present study. Two doses of the extract were chosen according to our previous studies [ 12 , 20 , 21 , 36 ] which showed its minimum and maximum effects.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…At present, plant therapy for AD has attracted more and more attention because of its comprehensive effects and less side effects ( Mithu et al, 2014 ; Sun et al, 2014 ; Yan et al, 2017 ; Martínez-Coria et al, 2019 ; Singh et al, 2019 ; Baranowska-Wójcik et al, 2020 ; Hosseini et al, 2021 ; Nowak et al, 2021 ; Sohn et al, 2021 ; Anupama et al, 2022 ). The mystery fruit, which we used in this study, has also received more attention due to its good antioxidant properties, including lowering cholesterol ( Huang et al, 2020 ), antidiabetic effects ( Obafemi, et al, 2019 ), reducing serum uric acid levels ( Shi et al, 2016 ), and anti-oxidative damage ( Chen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, because of the clinical trial failures and multiple sides of synthetic drugs, the development of phytotherapy has received close attention from the public and the scientific community ( Vegh, et al, 2019 ). Many foods and nutritional drugs are claimed to have memory-improving effects, including Ginkgo biloba ( Singh, et al, 2019 ; Nowak, et al, 2021 ), dihydromyricetin ( Martínez-Coria, et al, 2019 ), linalool ( Hosseini et al, 2021 ), fig leaves ( Sohn et al, 2021 ), Schisandra polysaccharides ( Sun et al, 2014 ), Nardostachys jatamansi ( Anupama et al, 2022 ), tea ( Baranowska-Wójcik, et al, 2020 ), Forsythia ( Yan et al, 2017 ), curcumin ( Mithu et al, 2014 ), and acidic polysaccharose ( Mithu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%